The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Proceedings of the 35th Annual Meeting on Association for Computational Linguistics - 1997
DOI: 10.3115/976909.979640
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the semantic orientation of adjectives

Abstract: We identify and validate from a large corpus constraints from conjunctions on the positive or negative semantic orientation of the conjoined adjectives. A log-linear regression model uses these constraints to predict whether conjoined adjectives are of same or different orientations, achieving 82% accuracy in this task when each conjunction is considered independently. Combining the constraints across many adjectives, a clustering algorithm separates the adjectives into groups of different orientations, and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
309
1
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 738 publications
(317 citation statements)
references
References 19 publications
1
309
1
6
Order By: Relevance
“…Previous work on unsupervised sentiment classification has shown that adjectives and adverbs are good indicators of sentiment (Hatzivassiloglou, 1997(Hatzivassiloglou, , 2000, [19], Turney 2002 [5]). It has also been shown that adjectives present around a given topic are indicative of sentiment related to the particular topic [11], [20].…”
Section: ) Default Classifiermentioning
confidence: 99%
“…Previous work on unsupervised sentiment classification has shown that adjectives and adverbs are good indicators of sentiment (Hatzivassiloglou, 1997(Hatzivassiloglou, , 2000, [19], Turney 2002 [5]). It has also been shown that adjectives present around a given topic are indicative of sentiment related to the particular topic [11], [20].…”
Section: ) Default Classifiermentioning
confidence: 99%
“…One of the key ideas is the one proposed by Hazivassiloglou and McKeown [34]. The technique starts with a list of seed opinion adjective words, and uses them and a set of linguistic constraints or conventions on connectives to identify additional adjective opinion words and their orientations.…”
Section: Corpus-based Approach and Sentiment Consistencymentioning
confidence: 99%
“…For example, sentences (1), (2), (6) and (8) do not express any opinions. The issue of subjectivity has been extensively studied in the literature [34,35,79,80,97,99,100,102,103,104].…”
Section: Objective Of Mining Direct Opinionsmentioning
confidence: 99%
“…Notice that AUC is for binary class problems only thus we report the Kappa statistics instead, which intuitively measures the incremental performance of a classifier with respect to the baseline accuracy 7 . The baseline accuracy is the accuracy of randomly guessing the sentiment class, and in the three class problem the expected accuracy is 33.33%.…”
Section: Inputmentioning
confidence: 99%
“…A related problem is that of studying the semantic orientation, or polarity, of words as defined by Osgood et al [6]. Hatzivassiloglou and McKeown [7] built a log-linear model to predict the semantic orientation of conjoined adjectives using the conjunctions between them. Huettner and Subasic [8] hand-crafted a cognitive linguistic model for affection sentiments based on fuzzy logic.…”
Section: Related Work On Sentimentsmentioning
confidence: 99%